Palladium-catalyzed electrophilic C–H fluorination of arenes using oxazoline as a removable directing group. Issue 48 (30th November 2016) - Gutierrez, David A.; Lee, Wan-Chen Cindy; Shen, Yuning; Li, Jie Jack
Graphical abstract: Highlights: For the first time, the old directing group dimethyloxazoline, which was used to direct ortho -lithiation has now been applied in palladium-catalyzed C–H fluorination. Combination of Ag(NO3 )2 and AgNO3 greatly promoted the C–H fluorination. The removable directing group may be unmasked readily via hydrolysis. Abstract: Dimethyloxazoline was rationally designed to act as a removable ortho -directing group (DG) for the palladium-catalyzed C–H electrophilic fluorination of arenes. Using NFSI as the fluorinating agent, and Pd(II), Ag(I) catalytic system, electrophilic C(sp 2 –H) ortho -fluorination took place on a variety of aryl substrates to afford the corresponding mono- and di-fluorinated products.